Role of Vitamin K2 in Human Body: A Mini Review (Iraqi Journal of Medical Sciences, 2024)
Vitamin K2 (Menaquinone) stands out from other members of the vitamin K family due to its unique molecular structure. It is primarily found in meat and dairy products or converted from K1 in the gut. The conversion process of K1 to K2 in animal tissues, along with the role of intestinal bacteria in K2 production, is crucial for maintaining adequate levels. Extensive research has highlighted the importance of vitamin K2 in promoting bone health, preventing arterial calcification, and enhancing cardiovascular health. Additionally, vitamin K2 supports fertility and growth, and is associated with reducing the risk of cardiovascular diseases and certain cancers.Keywords: Vitamin K2, bone, osteocalcin, calcificationCitation: Ahmed MH, Hashim ZH. Role of vitamin K2 in human body: A mini review. Iraqi JMS. 2024; 22(2): 188-193. doi: 10.22578/IJMS.22.2.1
Keywords: Vitamin K2; bone; osteocalcin; calcification